Erythrocyte pyruvate kinase deficiency: 2015 status report. Issue 9 (14th August 2015) - Grace, Rachael F.; Zanella, Alberto; Neufeld, Ellis J.; Morton, D. Holmes; Eber, Stefan; Yaish, Hassan; Glader, Bertil
<x xml:space="preserve">Abstract</x> Over the last several decades, our understanding of the genetic variation, pathophysiology, and complications of the hemolytic anemia associated with red cell pyruvate kinase deficiency (PKD) has expanded. Nonetheless, there remain significant gaps in our knowledge with regard to clinical care and monitoring. Treatment remains supportive with phototherapy and/or exchange transfusion in the newborn period, regular or intermittent red cell transfusions in children and adults, and splenectomy to decrease transfusion requirements and/or anemia related symptoms. In this article, we review the clinical diversity of PKD, the current standard of treatment and for supportive care, the complications observed, and future treatment directions.Am. J. Hematol. 90:825–830, 2015. © 2015 Wiley Periodicals, Inc.